Ante Pío XII y Mons. Montini. Audiencias a miembros del Opus Dei, en los diarios de José Orlandis (1942-1945) / Before Pius XII and Msgr Montini. Audiences with members of Opus Dei in the diaries of José Orlandis - Josep-Ignasi Saranyana (Studia et Documenta)
From June 1942 until August 1945, Pius XII received five members of Opus Dei in private audience. In cronological order these were: José María Albareda, José Orlandis, Salvador Canals, Francisco Botella and Álvaro del Portillo. Pius XII obtained from them information about the nature and apostolic activities of the Work of God. Álvaro del Portillo, José Orlandis and Salvador Canals were also received by Giovanni Battista Montini, at the time Substitute of the Secretary of State, on various occasions. The investigation is based on original sources from de General Archive of the Prelature. There are eleven exclusive documents related to these audiences included in an appendix.